Application of improved ACM model to the design by hand of CMOS analog circuits. (January 2022) - de Jesus Costa, Ademir; Mehdipour, Eliyas; Santana, Edson Pinto; Araújo Cunha, Ana Isabela
Abstract: This work aims to provide solutions and perspectives for CMOS analog designers by reducing the time spent in iteratively dimensioning the devices and simulating the circuits. For this purpose, by-hand design methodologies for a few analog cells are proposed employing a MOSFET compact model which has been earlier improved by adding sub-models for some second order effects. A semiempirical sub-model and characterization method is presented for the Early voltage, thus enhancing the set of model equations for hand calculations. The accomplishment of several by-hand design examples and the comparison between simulation results and specifications succeeded in demonstrating the usefulness and advantages of using the improved MOSFET compact model in the proposed methodologies.